2018
DOI: 10.3892/or.2018.6403
|View full text |Cite
|
Sign up to set email alerts
|

Insufficient radiofrequency ablation promotes hepatocellular carcinoma cell progression via autophagy and the CD133 feedback loop

Abstract: Insufficient radiofrequency ablation (iRFA) often leads to residual hepatocellular carcinoma (HCC) progression. However, the mechanism is still poorly understood. In the present study, we demonstrated that LC3B protein expression levels were significantly increased in the residual hepatocellular carcinoma cells after radiofrequency ablation (RFA) treatment in vivo. Moreover, iRFA promoted autophagy, autophagosome formation and autophagic flux in Huh-7 and SMMC7721 cell lines in vitro. In addition, iRFA induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 33 publications
2
23
0
Order By: Relevance
“…Therefore, whether autophagy promotes cell survival or induces cell death depends on the cell type and environmental stress. Our team previously reported that IRFA promotes HCC cell progression via autophagy and the CD133 feedback loop [13]. In this study, we found that inhibition of heat stressinduced autophagy enhances heat-induced apoptosis both in vitro and in vivo.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Therefore, whether autophagy promotes cell survival or induces cell death depends on the cell type and environmental stress. Our team previously reported that IRFA promotes HCC cell progression via autophagy and the CD133 feedback loop [13]. In this study, we found that inhibition of heat stressinduced autophagy enhances heat-induced apoptosis both in vitro and in vivo.…”
Section: Discussionsupporting
confidence: 54%
“…Previous studies showed that sublethal heat stress induces autophagy in several human cancer cell lines, such as HeLa and A549 cells [12]. Recent studies reported that IRFA promotes the progression of residual HCC via autophagy [13,14]. These findings strongly support a correlation between autophagy and HCC progression after IRFA.…”
Section: Introductionsupporting
confidence: 53%
“…A combination of these treatments with an autophagy inhibitor (e.g. (hydroxy)chloroquine, 3-MA and Lys05) was associated with enhanced tumour cell necrosis and apoptosis, [148][149][150][151] suggesting that inhibiting autophagy to target residual tumour cells could be beneficial. Moreover, autophagy is implicated in tumour cells' resistance to systemic treatments.…”
Section: Targeting Autophagy In Hepatocellular Carcinoma: a Complex Amentioning
confidence: 99%
“…The main mechanism is that the proliferation of cancer cells is accompanied by the increase of nutritional requirements, so that autophagy will be activated to provide tumor cells with nutrients and energy (28). Meanwhile, autophagy can enhance the chemoradiotherapy resistance of tumor cells (29). With our results, we guessed that autophagy may play a role in promoting the developing of LIHC, or the existence of LIHC may enhance the autophagy.…”
Section: Discussionmentioning
confidence: 78%